A contratualidade da reversão de bens nas concessões de serviços públicos - Simas, Renata Regiane Lacerda (2023)
This study deals with the reversal of assets in permits and common concession contracts for public services and in sponsored concession contracts in public-private partnerships. Its main aim is to analyze some doubts and discussions faced by the Granting Authority and delegates of public services concerning the reversal of assets due to the termination of the contractual relationship, which are evidenced after more than 25 years of the Concessions Law (Law No. 8987/1995) because of the lack of clarity and objectivity of contractual instruments regarding the identification of reversible assets. It also proposes an analysis of this institute from a new perspective, with an expanded reading of the concept in view of the evolution of public service concessions regarding the following: (i) the need for reversible assets in permits and common concession contracts for public services and in sponsored concession contracts in public-private partnerships; (ii) obligation of asset reversal clause in contractual instruments; (iii) what such instruments should contain to avoid doubts and discussions; and (iv) the close relationship between the institute of reversal of assets and the economic-financial balance of the contracts. In conclusion, this study shows that the definition of clear and precise rules before signing the granting instrument is crucial to allow bidders to present price proposals that consider all the burdens and bonuses of the project, ensuring legal certainty and avoiding numerous and costly administrative, judicial and arbitration discussions